Quantum physics - Le Bellac, Michel (Cambridge University, 2006)
Textbook for a modern course on quantum physics for advanced undergraduate and graduate students.
Translation from the French.
Keywords: Quantum theory.; Physics.; Théorie quantique.; Physique.; physics.; SCIENCE -- Physics -- Quantum Theory.; Physics; Quantum theory; Quantenmechanik